Cost estimates of producing purple passionfruit in south Florida - Trent Blare; Victor Contreras; Fredy H. Ballen; Joshua D. Anderson; Jonathan H. Crane; Nicholas Haley (EDIS)
This publication examines the estimated costs and returns of an established purple passionfruit orchard in south Florida. The information presented in this publication was collected through field interviews with growers and industry specialists. It is based on a variety of production practices on small scale farms (1-2 acres). The information is intended only as a guide to estimate the financial requirements of running an established passionfruit planting. We estimated that the average net return of an established passionfruit (purple) plantation in south Florida is approximately $2,562/acre, or $0.92/pound.